1977
DOI: 10.1093/oxfordjournals.jbchem.a131778
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gastrointestinal and Related Hormones on Glycogenolysis and Gluconeogenesis in Cultured Liver Cells1

Abstract: When isolated rat liver cells were incubated for 15 min in the presence of vasoactive intestinal peptide, secretin, gastrin, caerulein or glucagon at concentrations ranging from 0.2 microgram to 2 microgram per ml, glycogenolysis was stimulated. Among the gastrointestinal hormones or peptides tested, vasoactive intestinal peptide had the highest stimulatory activity. However, somatostatin was inhibitory for liver glycogenolysis. Combination experiments showed that somatostatin also inhibited the stimulatory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…The increased plasma VIP levels found while running are in accordance with previous reports that VIP increases during endurance exercise (18,22,34,35). The increase in plasma VIP levels during exercise, as for the other substrate-mobilizing hormones, may be explained by VIP's proposed role as a polypeptide of substrate need and is supported by its ability to stimulate lipolysis (16), glycogenolysis, and gluconeogenesis (31). Studies by Galbo et al (18), Oktedalen and colleagues (34,35), and Opstad (36) have reported that the VIP response to exercise is almost abrogated by glucose ingestion or infusion during exercise, suggesting that VIP has an energy-mobilizing function during exercise.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The increased plasma VIP levels found while running are in accordance with previous reports that VIP increases during endurance exercise (18,22,34,35). The increase in plasma VIP levels during exercise, as for the other substrate-mobilizing hormones, may be explained by VIP's proposed role as a polypeptide of substrate need and is supported by its ability to stimulate lipolysis (16), glycogenolysis, and gluconeogenesis (31). Studies by Galbo et al (18), Oktedalen and colleagues (34,35), and Opstad (36) have reported that the VIP response to exercise is almost abrogated by glucose ingestion or infusion during exercise, suggesting that VIP has an energy-mobilizing function during exercise.…”
Section: Discussionsupporting
confidence: 90%
“…Exercise-mediated increases in VIP are thought to act through reperfusion of splanchnic blood flow (29, 36). VIP has been described as a "hormone of need" in that its secretion is increased during starvation and exercise and is associated with increases in glycogenolysis, lipolysis, and hepatic gluconeogenesis (16,31). Increased VIP levels do not correlate, however, with low blood glucose levels (36).…”
mentioning
confidence: 99%
“…Such effects have been sought in various systems, including isolated rat hepatocytes (10,21,22), perfused rat liver (23,24), liver slices (25), isolated rat adipocytes (20), rat hemidiaphragm (26), and perfused rat hindquarter (20). In the most comprehensive study (20), the Nashville group demonstrated no effect of somatostatin on glucose uptake by the perfused rat hindquarter in the presence or absence of insulin, confirming previous results with the rat hemidiaphragm (26).…”
Section: Glucose Metabolismsupporting
confidence: 70%
“…Similar conclusions were obtained with liver slices (25) and the isolated perfused liver (23). At very high concentrations somatostatin has been noted to influence glucagon-stimulated glucose production (21,22,24), effects not seen in other studies with lower levels of the peptide. There is thus considerable information to suggest that any influence of somatostatin on glucose metabolism in vivo in fasting subjects is mediated through changes in hormone secretion.…”
Section: Glucose Metabolismmentioning
confidence: 61%
“…The biological effects of VIP stim ulation, however, differ in the target cells. For example, VIP induces alterations in water and electrolyte transfer in intestinal epithelial cells [18], whereas it stimulates glycogenolysis in hépatocytes [19]. VIP has also been re ported to have a capacity to modulate the functions of lymphocytes [9] and natural killer cells [10].…”
Section: Discussionmentioning
confidence: 99%